The role of YWHAZ in cancer: A maze of opportunities and challenges - Gan, Yun (J Cancer, 2020)
YWHAZ (also named 14-3-3ζ) is a central hub protein for many signal transduction pathways and plays a significant role in tumor progression. Accumulating evidences have demonstrated that YWHAZ is frequently up-regulated in multiple types of cancers and acts as an oncogene in a wide range of cell activities including cell growth, cell cycle, apoptosis, migration, and invasion. Moreover, YWHAZ was reported to be regulated by microRNAs (miRNAs) or long non-coding RNAs and exerted its malignant functions by targeting downstream molecules like protein kinase, apoptosis proteins, and metastasis-related molecules. Additionally, YWHAZ may be a potential biomarker of diagnosis, prognosis and chemoresistance in several cancers. Targeting YWHAZ by siRNA, shRNA or miRNA was reported to have great help in suppressing malignant properties of cancer cells. In this review, we perform literature and bioinformatics analysis to reveal the oncogenic role and molecular mechanism of YWHAZ in cancer, and discuss the potential clinical applications of YWHAZ concerning diagnosis, prognosis, and therapy in malignant tumors.